Pengaruh Pengendalian Intern, Komitmen Organisasi Dan Kompetensi Sumber Daya Manusia Terhadap Sistem Informasi Akuntansi Penerimaan Kas Pada PT. Mandala Adhi Perkasa Sejati Semarang - Gilbert Daniel Ricardo; Sutono Sutono (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2022)
This study aims to analyze the effect of internal control, organizational commitment, human resource competence on cash receipts accounting information systems. The population in this study amounted to 183 people. The sample in the study was 40 using the method purposive sample. Hypothesis testing is known that the value of t arithmetic for internal control (X1) = 5,300 > t table 2,028 and level of significance 0,000 < 0,05 with β1 = 0,618 in a positive direction, meaning that internal control (X1) significant positive effect on the cash receipts accounting information system, then hypothesis 1 is accepted. t count for organizational commitment (X2)= 3,890 > t table 2,028 and level of significance 0,000 < 0,05 with β2= 0,365 ait means that organizational commitment has a significant effect on the cash receipts accounting information system, then hypothesis 2 is accepted. t count for human resource competence (X3)= 2,266 > t table 2,028 and level of significance 0,03 < 0,05 with β3= 0,194 with a positive direction means that the competence of human resources has a significant positive effect on the cash receipts accounting information system, so hypothesis 3 is accepted.